Julius Caesar - Shakespeare, William, 1564-1616 (New York : Barron's Educational Series, 2002)
Presents the original text of Shakespeare's play side by side with a modern version, with discussion questions, role-playing scenarios, and other study activities.
"Original Shakespearean text, with a modern line-for-line translation."
Includes bibliographical references (245-249).
Keywords: Shakespeare, William, -- 1564-1616.; Caesar, Julius -- Assassination -- Drama